Copolymerized carbon nitride nanoparticles for near-infrared II photoacoustic-guided synergistic photothermal/radiotherapy - Wu, Min; Huang, Yuxin; Huang, Xiaoyu; Wang, Fu; Wei, Xunbin (Frontiers in Chemistry, 2023)
Nanotheranostic agents that integrate diagnosis and treatment are promising for precision medi-cine, but they encounter some obstacles such as penetration depth and efficiency. In this study, novel carbon nitride-rose bengal nanoparticles (CN-RB NPs) with a graphite carbon nitride skel-eton were synthesized by one-step thermal copolymerization. The enhanced absorption in the near-infrared-II region (NIR-II) endows CN-RB NPs with an excellent photothermal effect under 1064 nm laser irradiation, as well as an obvious photoacoustic signal for imaging in vivo. Inter-estingly, due to the introduced iodine element, CN-RB NPs exhibit enhanced radiation therapy, indicating that CN-RB NPs can achieve ideal therapeutic outcome through collaborative photo-thermal/radiation therapy under the guidance of NIR-II photoacoustic imaging. Moreover, CN-RB NPs demonstrate minimal side effects and long-term biological stability after 14 days. Therefore, the proposed new multifunctional nano-platform CN-RB NPs hold great potential in the application of deep therapeutics.